2016
DOI: 10.1016/j.ypmed.2016.06.023
|View full text |Cite
|
Sign up to set email alerts
|

Using behavioral economic theory to increase use of effective contraceptives among opioid-maintained women at risk of unintended pregnancy

Abstract: Objective An unsettling aspect of the US opioid epidemic is the high rate of in utero exposure, especially since most of these pregnancies are unintended, due in part to low rates of effective contraceptive use among opioid-using women. This study tested an intervention informed by behavioral economic theory and aimed at promoting effective contraceptive use among opioid-maintained women at risk of unintended pregnancy in the Burlington, VT area between 2011–2013. Methods Thirty-one women were assigned (init… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 38 publications
2
38
0
Order By: Relevance
“…Overall, we found that almost half the women attending the OAT program were potentially eligible for the contraception clinic and that most were supportive of the provision of contraception services within the OAT, yet few presented. A small randomised controlled trial in the US found contingency management effective at engaging women receiving OAT in contraceptive care, with 56% of women in the intervention group using LARC at six months compared to 7% in the control group and no reported pregnancies 15 . This approach requires further exploration in the Australian context, where overall patterns of contraceptive use are similar 4 .…”
Section: Resultsmentioning
confidence: 99%
“…Overall, we found that almost half the women attending the OAT program were potentially eligible for the contraception clinic and that most were supportive of the provision of contraception services within the OAT, yet few presented. A small randomised controlled trial in the US found contingency management effective at engaging women receiving OAT in contraceptive care, with 56% of women in the intervention group using LARC at six months compared to 7% in the control group and no reported pregnancies 15 . This approach requires further exploration in the Australian context, where overall patterns of contraceptive use are similar 4 .…”
Section: Resultsmentioning
confidence: 99%
“…41,42 Only one study reported a consistent and significant effect of financial incentives on LARC use during a 6-month follow-up (g=1.282-2.385, p<0.05), but the effect on unintended pregnancy rate was comparable to usual practice (g=-1.196, p=0.153). 33 Three motivational interventions had a moderate but significant effect on adherence to regular contraceptive use at 3-month follow-up. 19,26,29 The effect of motivational interventions on contraceptive use was quite stable and moderate (g ranged between 0.274 and 0.684, p<0.05) at 6 and 9 months post-intervention.…”
Section: Intervention Outcomesmentioning
confidence: 93%
“…A study conducted by Heil et al found that financial incentives had the most pronounced effect on unintended pregnancy prevention, compared with dissemination of written information. 33 However, participants were not randomly assigned to the intervention group and the sample size was relatively small (n=31). In recent decades, there have been many debates regarding the ethics of providing financial incentives to women with addiction problems to start LARCs or accept sterilization.…”
Section: Main Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…In a creative and important effort to prevent unwanted pregnancies, Heil et al (2016—in this issue) demonstrate the efficacy of a behavioral economic intervention that combines financial incentives with a World Health Organization intervention for making effective contraception easier to access. The incentives are not provided contingent on using the contraceptives.…”
Section: Leveraging Behavioral Sciencementioning
confidence: 99%